Effectiveness Of MBCT Therapy in Improving Psychological Well-Being in NSSI (Non-Suicidal Self Injury) Survival in The City of Bandung - Prinska Damara Sastri; Pratidina Ekanesia; Rifqi Farisan Akbar; Dyanadhila Syadzwina (Westscience Press, 2023)
This study aims to determine whether MBCT therapy has an effect on improving the psychological well-being of NSSI survivors in the city of Bandung. The sampling technique used is non-probability sampling – purposive sampling. The study was conducted on three NSSI survivor participants who had a decrease in things psychological well-being. This study uses a measuring instrument Ryff Scales of Psychological Well-Being by Carol D. Ryff, and the interview method. The research results show that Mindfulness-Based Cognitive Therapy increases psychological well-being, Mindfulness-Based Cognitive Therapy improves aspects of autonomy and personal growth, as well as aspects of mindfulness influential is non-judgmental and patient.